Relationship between juvenile idiopathic arthritis and temporomandibular disorders: a literature review (Research, Society and Development, 2021)
The aim of this article was to conduct a review on Juvenile Idiopathic Arthritis (JIA), highlighting the impairment of the temporomandibular joints (TMJs) and the orofacial consequences of this pathology, including its possible relationship with signs and symptoms of Temporomandibular Disorders (TMDs), as well as the indicated therapeutic approaches. A search for articles was carried out in the “Pubmed” and “SciELO” databases from November 2018 to January 2019 using the following descriptors: «temporomandibular joint (TMJ) AND arthritis», «Juvenile idiopathic arthritis (JIA) AND treatment AND JIA »and« orofacial AND manifestations AND JIA »and their respective in Portuguese. Inclusion criteria were articles describing JIA in the TMJ, with an emphasis on diagnosis, consequences and treatment. The exclusion criteria were given by bibliographic relevance, articles with publications prior to 2012 and articles without full access to the content. Hundred complete articles were obtained, of which 21 were used as an appropriate scientific basis, after analysis and selection and obeying the inclusion and exclusion criteria. A book was considered relevant to the research. JIA constantly affects the temporomandibular joints causing various types of orofacial changes and dysfunctions in that joint. Early diagnosis is difficult, but of paramount importance, as it aims to minimize future complications, both at the occlusal level, as well as interfering with the normal growth of the mandible. The differential and early diagnosis between TMD and JIA is extremely important, as it will serve as a basis for choosing the most appropriate treatment for these patients.